Bullous pemphigoid: Management during COVID-19 pandemic - Ajit B Janagond; Anusha Lingaiah; Arun C Inamadar (Wolters Kluwer Medknow Publications, 2021)
Bullous pemphigoid (BP) is an autoimmune blistering disorder with subepidermal split, which predominantly affects the elderly. Here, we report a case of BP with hypertension and bronchial asthma managed during coronavirus disease-2019 national lockdown. A known case of BP in remission for 10 months came with recurrence. The patient was managed with dapsone and topical corticosteroids. Social media application was utilized further to prescribe and monitor the patient due to inconvenience faced during the current pandemic.